Epidemiology of lung cancer in Northern Greece: An 18-year hospital-based cohort study focused on the differences between smokers and non-smokers - Domvri, Kalliopi (Tob Induc Dis, 2020)
INTRODUCTION: Lung cancer remains a leading cause of cancer incidence, yet, in Greece, country-level registry-based data are limited. We have thus investigated the epidemiology of lung cancer and its trends in the George Papanikolaou Hospital, Northern Greece over 18 years (2000–2018). METHODS: We analyzed all the cases reported in the Bronchoscopy Unit of the Hospital for the period 2000–2018. In total, 15131 subjects (12300 males and 2831 females) that presented with a mass in the imaging, were submitted to bronchoscopy. Characteristics of patients such as age, sex, smoking history and occupation were collected. Statistical analysis was performed with SPSS 21.0 software package. RESULTS: Among all subjects, a total of 5628 (37.2%; mean age: 65.85 ± 9.6 years) cases of primary lung cancer were identified with a male to female ratio of 2:1 (41.1% to 20.4%) (p<0.001). Squamous cell lung cancer was the most common type of lung cancer identified in this population (44%) with a higher proportion in males compared to females (p<0.001). Furthermore, adenocarcinoma was mostly observed in female non-smokers compared to males (p<0.001). The majority of lung cancer cases were identified in patients occupied with agriculture and livestock breeding (41.1%). The mean age at lung cancer diagnosis was 66.13 ± 9.19 years for the whole study population. Lung cancer cases observed with a higher mean of 43.93 ± 10.84 years of smoking compared to cancer-free patients with 39.64 ± 13.23 years of smoking (p<0.001). CONCLUSIONS: Apart from smoking, demographic characteristics including age, sex and occupation appear to have an impact on lung cancer development in this population. Smoking history alone could not predict the development of lung cancer in the studied northern Greek population.